An Analysis and Measurement of Employee Engagement level for Human Resource Division Improvement: Case Study at PT. Dasindo Media, Bandung Branch - Sutanto, Hendra William; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2013)
Employee Engagement has been sounding recently as one of the issues in Human Resource business practices. Dale Carnegie Training as one of the training provider in Indonesia, under the management of PT. Dasindo Media, provides the training programs that help the company to engage more with their employees and treat them as valuable asset. However, as a learning organization, Dale Carnegie Training Bandung also faces the engagement issue within internal of the company. The early research found out that since the year of 2009, there has been unstable sales performance, unhappy working conditions, and high turnover in sales team. As research being done within internal company, it found out that there are four elements of employee engagement model issues that interfere the sales performance, they are: company, total rewards, people, and work factor. A further study is being done for those factor by using Analytical Hierarchy Process method to determine the importance level, interview and structure questionnaire design to determine performance level, and both calculation brings out result for urgency priority level should be prioritize for Human Resource Division system change practices. The result of urgency level priority is to fix the total rewards and work factor, especially resource variable. Several possible solutions are brought out to fix the total rewards variable, such as designing proper pay structure and determining possible and fair benefit outcome to maintain fairness to each employee, and doing specific recruitment process to maintain work balance in achieving sales target. Â Keywords: employee engagement, Analytical Hierarchy Process, importance level, performance level, urgency priority level.